Peran Otoritas Jasa Keuangan Dalam Mengawasi Kegiatan Wakil Manajer Investasi Yang Menghimpun Dana Investor Melalui Reksa Dana - Pustaka, Reza; Keliduan, Kesli; Immanuel, Lianzen (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
The goal of national development is the creation of a just and prosperous society based on Pancasila and the 1945 Constitution. One of the activities that can support national development is the Capital Market. After the issuance of Law Number 4 of 2023 concerning Development and Strengthening of the Financial Sector, the functions, duties and authority over regulation and supervision were given to the Financial Services Authority. One of the authorities given to the Financial Services Authority is to grant business permits to Mutual Funds as a forum used to collect funds from the investing public or investors to then be invested in Securities Portfolios, collective investment portfolios, and/or other financial instruments by the Investment Manager. The person entitled to represent the interests of the Investment Manager in carrying out Securities Portfolio management activities is the Deputy Investment Manager. However, unfortunately, the clear regulations given to the Financial Services Authority based on Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector are for the supervision of Investment Managers and do not provide clear regulations for supervising the activities of Deputy Investment Managers.Keywords: Financial Services Authority; Capital Markets; Investment; Mutual Funds Abstrak Tujuan pembangunan nasional adalah terciptanya masyarakat adil dan makmur berdasarkan Pancasila dan UUD 1945. Salah satu kegiatan yang dapat menunjang pembangunan nasional adalah Pasar Modal. Pasca terbitnya Undang-Undang Nomor 4 Tahun 2023 tentang Pembinaan dan Penguatan Sektor Keuangan, fungsi, tugas, dan wewenang pengaturan dan pengawasan diserahkan kepada Otoritas Jasa Keuangan. Salah satu kewenangan yang diberikan kepada Otoritas Jasa Keuangan adalah memberikan izin usaha kepada Reksa Dana sebagai wadah yang digunakan untuk menghimpun dana dari masyarakat investor atau pemodal untuk kemudian diinvestasikan pada Portofolio Efek, portofolio investasi kolektif, dan/atau instrumen keuangan lainnya dengan cara: Manajer Investasi. Yang berhak mewakili kepentingan Manajer Investasi dalam melaksanakan kegiatan pengelolaan Portofolio Efek adalah Wakil Manajer Investasi. Namun sayangnya, pengaturan yang jelas yang diberikan kepada Otoritas Jasa Keuangan berdasarkan Undang-Undang Nomor 4 Tahun 2023 tentang Pembinaan dan Penguatan Sektor Keuangan hanya untuk pengawasan terhadap Manajer Investasi dan tidak memberikan pengaturan yang jelas untuk pengawasan terhadap kegiatan Deputi Manajer Investasi. Kata Kunci: Otoritas Jasa Keuangan, Pasar Modal, Investasi, Reksa Dana